Voltammetric method for the quantification of cadmium using non-commercial electrodes and minimal instrumentation - Vilasó Cadre, Javier Ernesto; Céspedes Martínez, Alejandro; Arada Pérez, María de los Ángeles; Baeza Reyes, José Alejandro (Eclética Química, 2019)
A voltammetric method for the cadmium quantification was developed using minimal instrumentation. A manual homemade potentiostat for linear voltammetry was used. An Ag reference electrode and auxiliary and working electrodes of writing graphite were employed for the electroanalysis. The electrolytic conditions for the quantification were stablished. Linearity, detection and quantification limits, precision and accuracy were evaluated. The conditions for the quantification were 1 mol/L of KCl as supporting electrolyte, pH 5 and 10 s for the current sampling. The range of quantification was from 10-3 to 1.5∙10-2 mol/L. The linear correlation (r), determination (R2) and adjusted (R2adj.) coefficients were 0.9986, 0.9972 and 0.9970. The detection and quantification limits were 3∙10-4 mol/L and 10-3 mol/L. Results showed an acceptable repeatability, with coefficients of variation from 1.5 to 5.8 % depending of the concentration. Uncertainty associated with the cadmium concentration was in the range of 1.2∙10-4 to 7∙10-5 mol/L, diminishing with the increasing of the concentration. A good accuracy was observed, with recoveries between 86.84 and 109.64 %.